ANALISIS YURIDIS PENERAPAN STRUKTUR DAN SKALA UPAH BERDASARKAN PERATURAN PEMERINTAH NOMOR 36 TAHUN 2021 - Nur Laila Ahmad; Lalu Husni (Private Law, 2023)
This study aims to examine the regulation of the structure and scale of wages based on Government Regulation Number 36 of 2021 concerning Wages as well as the legal consequences for companies that do not arrange and implement a wage structure and scale. This study uses the normative method. This research results reveal that the structure and scale of wages are arranged based on wage provisions in Indonesia. Based on the wage provision, the company arranges the structure and scale of wages and takes into account the company's readiness and capabilities. The legal consequences for companies that do not compile and implement the structure and scale of wages under applicable government regulations will impose administrative sanctions and criminal sanctions.